Pemanfaatan limbah padat Ikan Tuna melalui kegiatan budidaya Ikan Nila (Oreochromis niloticus), Studi kasus di Perusahaan abon UD Madurasa Kabupaten Manokwari - Dedi Ariana; Roni Bawole; Vera Sabariah (Cassowary, 2018)
The tuna waste in Manokwari has an economic potential that can be used as fish meal animal feed or fish feed. The aim of this study was to determine the chemical contents of tuna waste flour, examine of tuna waste meal, determine the feed test impact to the tilapia growth, analyze the impact of feed to water quality and analyze the feed manufacturing businesses. The study was conducted for six months (January to June 2015) at UD Madurasa. This study used, a completely randomized design with five treatments, there were feed A (control) and four test feeds formulated using tuna waste flour and bran (feed B, feed C, feed D and feed E). The feeds were tested using tilapia sized 5-8 cm and weighted 9-10 g in average (belo phase), then a 750 belos were used and allocated into 15 containers (50 belos / container). Feed was given twice a day in the morning (7:00 a.m. to 08:00) and afternoon (16:00 to 17:00) for six weeks. The feed amount was 5% of the body weight. The results show that tuna waste flour contain nutrients over the nutritional needs by tilapia. The tested feed has nutritional value better than feed A. Feed A has the highest efficiency and value of relative growth of 24.56% and 92.79%. Feed C has an efficiency of 22.83%, Feed E (20.37%), Feed B (19.30%) and Feed D (17.82%), also the growth of relative feed values of C (87.14%), Feed E (64.69%), Feed B (63.04%) and Feed D (55.53%). The variance analysis was not difference, however all feed gave same effect on tilapia growth. The tested feed did not pollute the water and categorized as 2nd and 3rd of water quality. It is assumed that this business is properly to be run with breakeven point will be achieved when sales reached to 8 kg (Rp 130,000.00) or at 4.5 months.